2018
DOI: 10.1515/jcim-2017-0172
|View full text |Cite
|
Sign up to set email alerts
|

Decreased anxiety after Dawood fasting in the pre-elderly and elderly

Abstract: Background A high prevalence of anxiety in the elderly often leads to decreased quality of life (QOL). A restrictive diet can increase the production of ketone bodies that encourage mood enhancement, neural protection and pain reduction. This study aimed to identify whether Dawood fasting could increase the QOL of the elderly by reducing anxiety. Methods This research was a quasi-experimental study involving a pretest–post-test control group design. The subjects were pre-elderly and elderly or healthy people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Our study shows a correlation between increased religiosity during the pandemic and endorsement of the statements "I meet my friends and family outside my household quite regularly" (this was forbidden at the time of the survey) and "At Easter, I adhered less strictly to the recommendations about not leaving home and not meeting other people". These observations may be taken to indicate that people who pray more are less fearful of the pandemic than others, and this is consistent with other research findings showing that religious people are characterized by low anxiety (Fidianingsih et al 2018). However, our study also identified some contradictions to such a portrayal, with people declaring that they had devoted more time to religious commitments during the pandemic also indicating that they had tried to take care of their immunity better than other respondents, and that they had worn masks more often than others (even when there was no obligation to do so).…”
Section: Discussionsupporting
confidence: 90%
“…Our study shows a correlation between increased religiosity during the pandemic and endorsement of the statements "I meet my friends and family outside my household quite regularly" (this was forbidden at the time of the survey) and "At Easter, I adhered less strictly to the recommendations about not leaving home and not meeting other people". These observations may be taken to indicate that people who pray more are less fearful of the pandemic than others, and this is consistent with other research findings showing that religious people are characterized by low anxiety (Fidianingsih et al 2018). However, our study also identified some contradictions to such a portrayal, with people declaring that they had devoted more time to religious commitments during the pandemic also indicating that they had tried to take care of their immunity better than other respondents, and that they had worn masks more often than others (even when there was no obligation to do so).…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, EGCG increases inhibition mediated through the GABA neurotransmitter, which would generate a similar activity to that caused by some medications, such as benzodiazepines [47][48][49], also decreasing levels of occasional anxiety and causing an anxiolytic effect, as observed after administering it in MS patients [28]. Completing this EGCG activity and based on mechanisms that trigger state anxiety, the action mechanism that ketone bodies have that improves anxiousness [19,20] is based on the inhibition of the activation of NMDA ionotropic glutamate receptors. These receptors have an essential role, not only on a cognitive level [50], but also regarding the presence of anxiety [51].…”
Section: Discussionmentioning
confidence: 96%
“…Particularly in MS, the ketone body β-hydroxybutyrate (BHB) activates HCA2 receptors expressed by neuroinflammatory cells, reducing neuroinflammation [17] and achieving a neuroprotective effect [18]. In addition, ketone bodies have decreased the perception of anxiety in animal models with Alzheimer's disease, where an anxiolytic effect of the ketogenic diet has been observed [19], and in humans of advanced age [20]. Regarding the nutrients capable of providing higher levels of ketone bodies in blood, those with high levels of medium-chain triglycerides (MCTs) stand out, with coconut oil possibly being the food with the highest amount of MCTs, due to the high percentages of medium-chain fatty acids (MCFAs), such as lauric acid, palmitic acid, stearic acid, myristic acid and oleic acid [21].…”
Section: Introductionmentioning
confidence: 99%
“…The fasting includes abstinence from eating, drinking, or smoking, and the recommendation is to start it with having a pre-dawn meal and to end it by eating iftar in the evening. Our previous study showed that although DF indicates no changes in the parameters of lipid profile, hematology [19], and quality of life among the elderly [20], there is a decrease in the oxidative stress and lipid profile among the mice given high carbohydrate and fat diets [21]. The purpose of this study is to prove the effect of DF on the changes in SOD, GPx, and Cat antioxidant enzymes in BALB/c strain mice.…”
Section: Introductionmentioning
confidence: 91%